« Don’t call me Nigger, Whitey » - Valérie Bonnet (Communication)
The aim of this article is to describe the steps of the Afro-American identity construction processes through an analysis of its self-designating words. These words are traces of self-categorization, and thus a constituting part of the Afro-American identity. The corpus is based on documents produced by the Afro-American population that have contributed to the construction of its identity: popular songs, founding political speeches, manifestos of the 1960s till today and online discussion groups.